PEMBERDAYAAN MASYARAKAT DALAM PEMBUATAN BRIKET UNTUK MENDONGKRAK UMKM DARI LIMBAH KAYU NON MAKANAN: PEMBERDAYAAN MASYARAKAT DALAM PEMBUATAN BRIKET UNTUK MENDONGKRAK UMKM DARI LIMBAH KAYU NON MAKANAN - Feri Tirtoni; Istiqomah; Bayu Rama Dhani (Universitas PGRI Adi Buana Surabaya, 2024)
This research aims to manufacture charcoal briquettes as an environmentally friendly alternative fuel. This research utilizes wood waste and citrus recycling. Aromatherapy briquettes are the latest innovation to increase the added value of charcoal briquettes which havebeen limited as the newest alternative energy. Aromatherapy briquettes are a mixture of charcoal powder and lime leaves. This study aims to increase the selling value of charcoal briquettes, as well as boost the economy of the people in Candiharjo village. The method used in this study is observation and interviews through several stages, starting from design, and observation of service targets. This research was produced as a solution to the constraints that existed in the village of Candiharjo in processing wood waste that had not pin used properly before. So in the manufacture of charcoal briquettes is expected to reduce wood waste and increase the selling value.